Modulation of root nodule antioxidant systems by nitric oxide : prospects for enhancing salinity tolerance in legumes - Liphoto, Mpho (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD(Agric) (Plant Biotechnology))--University of Stellenbosch, 2010.